2022
DOI: 10.1101/2022.07.13.499982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loop stacking organizes genome folding from TADs to chromosomes

Abstract: While population level analyses reveal significant roles for CTCF and cohesin in mammalian genome organization, their contribution to chromatin structure and gene regulation at the single-cell level remain incompletely understood. Here, we use chromosome tracing microscopy to measure the effects of removal of CTCF or cohesin on genome folding across genomic scales. We find cohesin contracts the chromosome into loops, facilitating contacts both within and between Topologically Associating Domains (TADs), while … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 97 publications
2
15
0
Order By: Relevance
“…It is also worth noting that ChromSTEM imaging captures the statistics of single cell organizational states, whereas the ensemble measurement of Hi-C is an aggregate statistic of many organizational states. Consequently, this suggested that mature packing domains were largely maintained independent of cohesin mediated loop formation but that the principal effect of RAD21 extrusion was on the production of a subset of nascent domains, possibly consistent with findings in prior reports using oligo-based methods( 20, 22 ).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…It is also worth noting that ChromSTEM imaging captures the statistics of single cell organizational states, whereas the ensemble measurement of Hi-C is an aggregate statistic of many organizational states. Consequently, this suggested that mature packing domains were largely maintained independent of cohesin mediated loop formation but that the principal effect of RAD21 extrusion was on the production of a subset of nascent domains, possibly consistent with findings in prior reports using oligo-based methods( 20, 22 ).…”
Section: Resultssupporting
confidence: 88%
“…4 ). Although this study has limitations in that it measures packing domains in sub-portion of one nucleus in each group, other studies have similarly showed the presence of TAD-like structures after cohesin degradation( 17, 2022, 25 ). While it is possible that TAD-like structures could be an observed subset of chromatin packing domains, the observed discordance between the number of lost TADs and the retention of most domains suggests otherwise.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…S5-6), we noticed that they are typically flanked by strong CTCF sites and, thus, located within, rather than next to, CTCF clusters. This organization might favour boundary bypass, TAD intermingling and communication with regulatory elements located on either side of the genes 26,27,31,78 . In contrast, for the two developmental genes that we investigated, we found no evidences indicating that CTCF clusters facilitate their expression or the communication with their cognate enhancers.…”
Section: Discussionmentioning
confidence: 99%